Study Abroad and Developing Reflective Research Practice Through Blogs: A Preliminary Study from the United Kingdom. Issue 3 (3rd July 2019) - Barrett, Giles Andrew; Hayes, Anne; Hollinshead, Jim
Abstract: Blogs are seen as an important strand of social networking and a significant way of disseminating research ideas and sharing knowledge and perceptions with new audiences via digital platforms. The use of blogs within off-campus activities, such as study abroad field visits, have the potential to enhance students' social media skills and confidence about becoming active researchers in public through communicating field research experiences and reflections on what they see, learn, hear, and do. Via a semi-structured questionnaire administered to UK-based university students participating in a recent Criminology program field visit to Slovenia in Europe, we assess the extent to which blogging facilitates student reflective practice on their lived experiences of undertaking research in culturally unfamiliar environments. We show that blogging combined with the whole experience of international fieldwork has a "learning gain" for students exemplified through a willingness to engage in reflective practice, self-awareness, and transferable skills.